Profiling of peripheral blood B-cell transcriptome in children who developed coeliac disease in a prospective study - Oras Astrid; Kallionpää Henna; Suomi Tomi; Koskinen Satu; Laiho Asta; Elo Laura; Knip Mikael; Lahesmaa Riitta; Aints Alar; Uibo Raivo; DIABIMMUNE Study Group (Elsevier Ltd, 2025)
Background
In coeliac disease (CoD), the role of B-cells has mainly been considered to be production of antibodies. The functional role of B-cells has not been analysed extensively in CoD.
Methods
We conducted a study to characterize gene expression in B-cells from children developing CoD early in life using samples collected before and at the diagnosis of the disease. Blood samples were collected from children at risk at 12, 18, 24 and 36 months of age. RNA from peripheral blood CD19+ cells was sequenced and differential gene expression was analysed using R package Limma.
Findings
Overall, we found one gene, HNRNPL, modestly downregulated in all patients (logFC −0·7; q = 0·09), and several others downregulated in those diagnosed with CoD already by the age of 2 years.
Interpretation
The data highlight the role of B-cells in CoD development. The role of HNRPL in suppressing enteroviral replication suggests that the predisposing factor for both CoD and enteroviral infections is the low level of HNRNPL expression.
Funding
EU FP7 grant no. 202063, EU Regional Developmental Fund and research grant PRG712, The Academy of Finland Centre of Excellence in Molecular Systems Immunology and Physiology Research (SyMMyS) 2012–2017, grant no. 250114) and, AoF Personalized Medicine Program (grant no. 292482), AoF grants 292335, 294337, 319280, 31444, 319280, 329277, 331790) and grants from the Sigrid Jusélius Foundation (SJF).